Aquaporins in development - a review - Wintour E Marelyn; Liu Huishu (BMC, 2005)
Abstract Water homeostasis during fetal development is of crucial physiologic importance. It depends upon maternal fetal fluid exchange at the placenta and fetal membranes, and some exchange between fetus and amniotic fluid can occur across the skin before full keratinization. Lungs only grow and develop normally with fluid secretion, and there is evidence that cerebral spinal fluid formation is important in normal brain development. The aquaporins are a growing family of molecular water channels, the ontogeny of which is starting to be explored. One question that is of particular importance is how well does the rodent (mouse, rat) fetus serve as a model for long-gestation mammals such as sheep and human? This is particularly important for organs such as the lung and the kidney, whose development before birth is very much less in rodents than in the long-gestation species.